1976
DOI: 10.1084/jem.144.6.1568
|View full text |Cite
|
Sign up to set email alerts
|

The binding of human lactoferrin to mouse peritoneal cells.

Abstract: Human iron-saturated Lf (FeLf), which was labeled with 125I or 50Fe, was found to combine with the membrane of mouse peritoneal cells (MPC) which consisted of 70% macrophages. The following experimental data suggested the involvement of a specific receptor. (a) The binding of FeLf to MPC reached a saturation point. (b) The binding of radioactive FeLf was inhibited by preincubating the cells with cold FeLf but not with human Tf, human aggregated and nonaggregated IgG, or beef heart cytochrome c (c) Succinylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(51 citation statements)
references
References 19 publications
(9 reference statements)
7
44
0
Order By: Relevance
“…Lactoferrin has been shown previously to bind to receptors on mononuclear phagocytes and to inhibit proinflammatory responses via NF-κB (39,54,55). Taken together with the evidence that apoptotic cells can suppress proinflammatory responses of mononuclear phagocytes and can elicit antiinflammatory responses by these cells (10,11), our results indicate that it is now reasonable to suspect that these effects are mediated, at least in part, by lactoferrin produced by apoptotic cells.…”
Section: Figuresupporting
confidence: 54%
“…Lactoferrin has been shown previously to bind to receptors on mononuclear phagocytes and to inhibit proinflammatory responses via NF-κB (39,54,55). Taken together with the evidence that apoptotic cells can suppress proinflammatory responses of mononuclear phagocytes and can elicit antiinflammatory responses by these cells (10,11), our results indicate that it is now reasonable to suspect that these effects are mediated, at least in part, by lactoferrin produced by apoptotic cells.…”
Section: Figuresupporting
confidence: 54%
“…There is now compelling evidence that lymphocytes are involved in the regulation of Fe metabolism, namely through the synthesis or specific binding of several "Fe-related proteins" [42][43][44][45]. In this context, lymphocyte CP expression gives additional support to the original postulate from De Sousa et al addressing a role for lymphocyte circulation in the regulation of Fe load [19] and establishes an additional link between immune system and Fe homeostasis.…”
Section: Discussionmentioning
confidence: 60%
“…In fact, it has been shown that the serotransferrins recognize specifically membrane receptors of the reticulocytes [50], that ovotransferrins recognize embryo bird cells [5 11 and that the lactotransferrins recognize the membrane receptors of human enterocytes [52]. The recognition of human lactotransferrin by the membrane receptors of the macrophages has been described by Van Snick et al [53]. This recognition may probably be mediated by the fucose residues, since Shepherd et al [54] have recently described the presence of fucose receptors on rat macrophages.…”
Section: Discussionmentioning
confidence: 98%